Disruption of RAB40AL function leads to Martin–Probst syndrome, a rare X-linked multisystem neurodevelopmental human disorder. Issue 5 (11th May 2012) - Bedoyan, Jirair Krikor; Schaibley, Valerie M; Peng, Weiping; Bai, Yongsheng; Mondal, Kajari; Shetty, Amol C; Durham, Mark; Micucci, Joseph A; Dhiraaj, Arti; Skidmore, Jennifer M; Kaplan, Julie B; Skinner, Cindy; et al.
Abstract : Background and aim: Martin–Probst syndrome (MPS) is a rare X-linked disorder characterised by deafness, cognitive impairment, short stature and distinct craniofacial dysmorphisms, among other features. The authors sought to identify the causative mutation for MPS. Methods and results: Massively parallel sequencing in two affected, related male subjects with MPS identified a RAB40AL (also called RLGP ) missense mutation (chrX:102, 079, 078-102, 079, 079AC→ GA p.D59G; hg18). RAB40AL encodes a small Ras-like GTPase protein with one suppressor of cytokine signalling box. The p.D59G variant is located in a highly conserved region of the GTPase domain between β-2 and β-3 strands. Using RT-PCR, the authors show that RAB40AL is expressed in human fetal and adult brain and kidney, and adult lung, heart, liver and skeletal muscle. RAB40AL appears to be a primate innovation, with no orthologues found in mouse, Xenopus or zebrafish. Western analysis and fluorescence microscopy of GFP-tagged RAB40AL constructs from transiently transfected COS7 cells show that the D59G missense change renders RAB40AL unstable and disrupts its cytoplasmic localisation. Conclusions: This is the first study to show that mutation of RAB40AL is associated with a human disorder. Identification of RAB40AL as the gene mutated in MPS allows for further investigations into the molecular mechanism(s) of RAB40AL and its roles in diverse processes such as cognition, hearing and skeletal development.